Abnormal spindle-like microcephaly-associated (ASPM) mutations strongly disrupt neocortical structure but spare the hippocampus and long-term memory. (January 2016) - Passemard, Sandrine; Verloes, Alain; Billette de Villemeur, Thierry; Boespflug-Tanguy, Odile; Hernandez, Karen; Laurent, Marion; Isidor, Bertrand; Alberti, Corinne; Pouvreau, Nathalie; Drunat, Séverine; Gérard, Bénédicte; El Ghouzzi, Vincent; et al.
Abstract: Autosomal recessive primary microcephaly results from abnormal brain development linked to proliferation defects in neural progenitors. The most frequent form, caused by ASPM mutations, is usually defined by a reduced brain volume and is associated with intellectual disability. Although many ASPM cases have now been reported, structural brain abnormalities and their link with cognitive disabilities have rarely been investigated. In this study, we used high resolution T1-weighted magnetic resonance imaging in seven patients with ASPM mutations and 39 healthy age-matched controls to quantify regional volumes, thickness, surface area, gyrification index and white matter volumes of 30 cortical regions. We observed a consistent reduction of 50% or more in the volume and surface area of all cortical regions except for the hippocampus and surrounding medial temporal structures, which were significantly less reduced. Neuropsychologic assessment indicated significant impairments of cognitive abilities. However, these impairments were associated with normal mnesic abilities, in keeping with the relative preservation of the hippocampus and medial temporal structures. These results show that, contrary to current opinion, the cortical volume and surface area of patients with ASPM mutations is reduced depending on a regionally specific fashion and their cognitive profile reflects this heterogeneity. The precise characterization of the cortical map and cognitive abilities of patients with ASPM mutations should allow developing more focused reeducative interventions well-suited to their real abilities.